Case Report: A myxoma with a far reach - Akiki, Elias; Arghami, Arman; Abbasi, Muhannad A.; El-Am, Edward A.; Ahmad, Ali; Foley, Thomas A.; Daly, Richard C.; Maleszewski, Joseph J.; Kurmann, Reto; Klarich, Kyle W. (Frontiers in Cardiovascular Medicine, 2024)
A 73-year-old female presented to the emergency department with a syncopal episode and history of dizzy spells. A transthoracic echocardiogram demonstrated a large left atrial mass extending into the right upper pulmonary veins. Subsequently, Cardiac Magnetic Resonance Imaging (CMRI) and Coronary Computed Tomography Angiography (CCTA) with 3D reconstruction and printing of the heart and mass were performed and demonstrated a high index of suspicion for an atypical left atrial myxoma. The mass was excised robotically, and pathology confirmed myxoma diagnosis..